Design and fabricate mini interceptor / Muhammad Firdaus Rozy - Rozy, Muhammad Firdaus (2022)
This era, we can see our country have a problem water pollution that worried because manyrubbishes that we can see on the water surface water areas. This project is design and fabrication about mini interceptor river cleaner, the problem that we find to do this project is a clean-up the river nowadays is difficult to do and many aspects to must be consider to use manpower. This project using a few methods to design which is build the 3 design and do the comparison before pick the best one between it. The design that chosen must be have a past the aspects durable, portable, easy to use, weight, safety, adjustment and buoyancy. The result of my project is I success to fabricate and design my project which is it float on the water surface but for it movement I try hard to build the circuit and coding but the movement cannot be activate. Recommendation for my project is we add another equipment for Arduino, and we recommend the more suitable design for front part of Mini Interceptor which can help to trapped trash more efficiently.